A systematic review of the determinants and the behaviour of equity risk premium - Chandorkar, Pankaj Avinash (Cranfield University, 2013)
Understanding the Equity Risk Premium (ERP) and the factors affecting it is cardinal to financial economics, particularly to equity research analysts, domestic and international institutional investors and financial economist. Since the seminal work of Mehra and Prescott (1985) there has been an exponential rise in the research explaining the reasons for ERP puzzle. This review, systematically, investigates the literature related to ERP in four key dimensions. The first dimension is regarding the issues related to different techniques of estimating the ERP. The second dimension is regarding the studies that explain the reasons of existence of the ERP puzzle by making modifications to the preference structures. The third is regarding the macroeconomic variables that help in predicting ERP and the fourth deals with studies that are conducted in the international context. In addition to this, this review meticulously captures some important limitations of the existing literature regarding the estimation of ERP and identifies the domestic and international determinants of ERP, in particular the UK ERP and proposes novel future directions of research. These future research directions have two important implications for my PhD. The first is the academic contribution that predominantly comes from methodological contribution of estimating the ERP. The second is the practical contribution that comes mainly from identifying the unique set of variables (UK domestic and international), which are of prime importance to the domestic and foreign institutional investors because of the financial crisis of 2008-2009 and which should affect the UK ERP.
Keywords: Equity premium; Equity premium puzzle; Habit formation; Rare disasters; Behavioural finance; Macroeconomics factors